Psychometric validation of the authorized Polish version of the Neck Disability Index. (29th April 2013) - Guzy, Grażyna; Vernon, Howard; Polczyk, Romuald; Szpitalak, Malwina
Abstract: Purpose : Psychometric validation of the authorized Polish version of the Neck Disability Index (NDI). Methods : Ninety-five patients with neck pain were enrolled. Reliability was assessed through Cronbach's alpha, split-half reliability, intra-class correlation (ICC) and agreement between measures with limits of agreement using the interval of 48 hours. Validity was determined by the Pearson correlation of the NDI with VAS. Responsiveness included mainly Pearson correlations of score changes on the NDI with the Global rating of change (GRC) scale. Minimal detectable change (MDC) and factor analysis were performed. The cut-point for the change, with its sensitivity and specificity, and the area under the curve were determined with the receiver operating characteristic (ROC) curve analysis. Results : Cronbach's alpha and split-half reliability were satisfactory. The ICC was 0.99. Bland and Altman analysis indicated an acceptable agreement between the measures. The correlation between the NDI and VAS was 0.55. Responsiveness estimated by the correlations between change scores of the NDI and GRC was −0.73 and −0.56. The MDC was 5.96. Factor analyses demonstrated a two-factor structure. The cut-point for detecting a change was 6.5. The sensitivity was 90% and specificity was 81%. Conclusions : The Polish version of the NDI showed good psychometric properties. It can be used both in clinical and research practice. Implications for Rehabilitation: The Polish version of the NDI, developed by MAPI Research Institute, was researched on a sample of 95 patients with neck pain. The psychometric properties of the adapted version of the NDI were satisfactory. The Polish version of the NDI proved to be useful in clinical practice as well as in research.